A look into online course withdrawal - Gnadt, Amanda S. (Kansas State University, 2013)
This study reviews the development of distance education, adult students and specifically looks at the reasons for online course withdrawal. The study specifically examines personal and course-related reasons distance students withdraw from courses. Online students who withdrew from a course were invited to complete a course withdrawal survey to provide additional information about why they withdrew. Students reported balance between coursework and work/family commitments most frequently as the primary reason for course withdrawal. Results indicated that students withdrawing because of work/family reasons have higher intentions of re-enrolling in the future. Faculty and staff response time was another reason reported for course withdrawal. A perceived delay in communication was related to course withdrawal. Results are discussed further and implications are addressed.
Keywords: Online course withdrawal; Distance education; Persistence; Adult Education (0516); Higher Education (0745)